Decolonial Metatextualities: Strategies of Resistance in Three Contemporary Novels of Oceania - Charon, Mylène; Lehartel, Temiti (eTropic: electronic journal of studies in the Tropics, 2023)
International audience Decolonial thinkers have stressed that to decolonise is not to reject the colonial legacy, but to deal with it, and to centre First Nations’ perspectives in its critique and in decolonising knowledge. As a critical relationship of a text – with itself, other texts, literature, and culture – metatextuality is a literary device operationalized in contemporary novels to resist persisting colonial powers. In this paper, we present three works of fiction by Indigenous writers of Oceania, and analyse their political use of metatextuality: L’île des rêves écrasés (Island of Shattered Dreams), by Tahitian author Chantal Spitz (1991); The Yield, by Aboriginal Wiradjuri novelist Tara June Winch (2019); and After Story, by Aboriginal Eualeyai/Kamillaroi writer Larissa Behrendt (2021). Centred on First Nations’ characters from Tahiti and Australia, these novels expose how they are racialised, marginalised, and constructed as inferior in postcolonising societies; and how, at the same time, these Indigenous characters are legitimate knowers and storytellers, reflecting on Western literature (often ironically), on their own marginality, and on their ancestral knowledges and languages. Borrowing from decolonial theorists Tlostanova and Mignolo’s (2012) ‘border thinking’, we propose that these novels deploy a ‘writing from the border’. Les penseur.se.s décoloniaux.ales soulignent que décoloniser ne signifie pas rejeter l’héritage colonial, mais y faire face en centrant les perspectives des Premières Nations. En tant que relation critique qu’un texte entretient avec lui-même, avec d’autres textes, avec la littérature et la culture en général, la métatextualité est un procédé littéraire employé dans les romans contemporains pour résister aux relations de pouvoir coloniales persistantes. Dans cet article, nous présentons trois œuvres de fiction par des autrices autochtones océaniennes et nous analysons leur emploi politique de la métatextualité : L’île des rêves écrasés (Island of Shattered Dreams) par ...